FORMATION OF FOREIGN LANGUAGE SPEECH COMPETENCE OF STUDENTS - Rakhmanova Nazokat Tairovna (American Journals, 2023)
The article reveals modern requirements for the formation of foreign language speech competence of students in the modern education. It is concluded that the importance of the ability to conduct oral communication in a foreign language.
Keywords: modern education, English language, speech competence, ability, pedagogical skill, innovative approach.